2019
DOI: 10.4102/ajod.v8i0.542
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of children with intellectual and developmental disabilities in inclusive schools in Accra, Ghana

Abstract: Background: Inclusive education is internationally recognised as the best strategy for providing equitable quality education to all children. However, because of the unique challenges they often present, children with intellectual and developmental disabilities (IDDs) are often excluded from inclusive schools. To date, limited research on inclusion has been conducted involving children with IDD as active participants.Objectives: The study sought to understand the experiences of children with IDDs in learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Even though it it was not known whose drawing was best, it was a laughter-filled class when some pupils' drawings had either one hand, one leg or one ear. This, though, confirms findings of Okyere, Aldersey & Lysaght (2019) regarding drawing characteristics of children with mental retardation. Once again, the three pupils drew the same drawings of themselves that they had drawn in previous weeks.…”
Section: Myselfsupporting
confidence: 89%
“…Even though it it was not known whose drawing was best, it was a laughter-filled class when some pupils' drawings had either one hand, one leg or one ear. This, though, confirms findings of Okyere, Aldersey & Lysaght (2019) regarding drawing characteristics of children with mental retardation. Once again, the three pupils drew the same drawings of themselves that they had drawn in previous weeks.…”
Section: Myselfsupporting
confidence: 89%
“…The teacher provided evidence to support their argument that most parent come to the school to insult or physically abuse teachers who dare to punish their children in the presence of their children. In support of this complaints, Okyere et al (2019) avers that such actions give the students the impression that they can do what they want hence such adolescent student define and adopt normal behaviour to their comfort. Other research work (Attila, 2018;Asante, 2019) on maladaptive behaviour in schools in the Ashanti region and other part of Ghana including Offinso Municipality revealed that students often feel insecure and afraid because teachers constantly threaten them with unexpected examination and failure.…”
Section: Background To the Studymentioning
confidence: 99%
“…Asante (2019) for his part observed that social discrimination by teachers creates inferiority on the part of some students which makes them to burst out with anti-social behaviours. To deal with such menace, researchers (Okyere et al, 2019) and practitioners alike (Gerade, 2019;Asante, 2019) have often argued that the solution to maladaptive behaviour can be more effective if school administration take up the mantle of developing strategies that will enable teachers to deal with such behaviours effectively. Though putting majority of the load on teachers and schools may seem unfair, (Gerade, 2019Nunan, 2018 argued that in contemporary times, students turn to spend much of their daily activities in school with their teachers, peers and school management especially those in boarding schools.…”
Section: Background To the Studymentioning
confidence: 99%
“…The above findings indicate that there has been a great deal of study on IE in Ghana but, as Okyere et al (2019) called for, there is the need to access the narratives of children living with disabilities in IE institutions within the country.…”
Section: Introductionmentioning
confidence: 95%
“…However, the notion of Pather (2019), regarding Inclusive Education in Africa, prevails in Ghana. According to Okyere, Aldersey and Lysaght (2019), Ghanaian policies are yet to pay the needed attention to teaching approaches and structural transformations to make IE a success. Earlier studies, such as the one by Boots and Owusu (2013) that focused on intellectual disability (IDD), found that only a few children access government-supported education.…”
Section: Introductionmentioning
confidence: 99%